2021
DOI: 10.1021/acsami.1c14950
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Working Mechanism of g-C3N4 as a Protection Layer for Lithium- and Sodium-Metal Anode

Abstract: The practical application of lithium-/sodium-metal batteries is currently hindered by severe safety issues caused by uncontrolled continuous dendrite growth. Semiconductive nanoporous g-C3N4 film has been demonstrated to be an effective protection layer for lithium-/sodium-metal anode, which can suppress the growth of dendrite. However, the underlying mechanism of how this semiconductive flexible thin film works to suppress dendrite growth remains unclear. In this work, we investigate the detailed working mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In these regards, carbon nitride (CN) is a promising material for artificial interphase due to its low electrical conductivity, high thermal stability, and ionic conductivity, as previously reported. [24][25][26][27][28][29][30][31] Moreover, CN itself is not an active material for sodium storage, 32 making it an even better candidate to be employed as a passivation layer. The in-plane structural pores (0.68 nm) might enable the diffusion of sodium ions while simultaneously blocking the negative counter ions.…”
Section: Introductionmentioning
confidence: 99%
“…In these regards, carbon nitride (CN) is a promising material for artificial interphase due to its low electrical conductivity, high thermal stability, and ionic conductivity, as previously reported. [24][25][26][27][28][29][30][31] Moreover, CN itself is not an active material for sodium storage, 32 making it an even better candidate to be employed as a passivation layer. The in-plane structural pores (0.68 nm) might enable the diffusion of sodium ions while simultaneously blocking the negative counter ions.…”
Section: Introductionmentioning
confidence: 99%
“…[3b,19] Nano-porous and highly lithiophilic/sodiophilic g-C 3 N 4 has emerged as an effective artificial protective layer in this context. [20] Moreover, flexible and mechanically stable polymers containing nitrogen functional groups are also favored, such as polythiourea, [21] and polyacrylonitrile. [22] While recent studies have shown significant improvements in battery performance using nitrogen-containing materials, the relevant studies are still rare and result-oriented which primarily concentrate on battery performance, giving less emphasis to comprehending the fundamental interactions between AMAs and those protective materials.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing appropriate photoelectric materials is the key to constructing a highly sensitive PEC sensing platform. Among numerous photoelectric materials, graphitic-like carbon nitride (g-C 3 N 4 ) has a band gap of 2.7 eV, which has attracted wide attention due to g-C 3 N 4 ’s excellent chemical stability, adjustable electronic structure, low price, convenient synthesis, and lack of toxicity. Unfortunately, the photoelectric performance of g-C 3 N 4 is limited by the quick recombination rate of photogenerated electron–hole pairs and its low specific surface area. In order to improve the photoelectric performance of g-C 3 N 4 , many researchers have focused on modifying g-C 3 N 4 to boost the charge separation through element doping, sensitization, and semiconductor coupling. , In particular, a semiconductor modified with metal nanoparticles (NPs) could effectively improve the photoelectric performance of the semiconductor for two reasons.…”
Section: Introductionmentioning
confidence: 99%